Tugas manusia di atas bumi menurut al-qur'an, hadis, dan sains modern - Islamiyah, Nur (Maliki Interdisciplinary Journal, 2026)
Human beings are special creations of Allah who hold a distinguished position among all of His creations. The Qur'an states that humans were created in the best form (QS. At-Tin [95]: 4) and entrusted with a great mandate to serve as Allah's servants ('abdullāh) as well as vicegerents (khalifah) on earth (QS. Al-Baqarah [2]: 30). These two roles affirm that humans have not only spiritual responsibilities to worship Allah but also social and ecological responsibilities to maintain environmental balance and uphold justice in the world. This study aims to comprehensively analyze human duties from the perspectives of the Qur'an, hadith, and modern science, as well as formulate their relevance in the context of modern life full of challenges. The findings reveal that human duties encompass three interconnected main aspects: first, as servants of Allah tasked with worship, piety, and devotion solely to Him; second, as vicegerents on earth tasked with managing, preserving, and sustaining the universe and its contents; third, as upholders of justice and truth in social life. Modern science, through concepts of ecosystems, sustainability, rational responsibility, and multiple intelligences, confirms and reinforces these human roles. Therefore, it can be concluded that the integration of revelation (Qur'an and hadith) with modern science offers a holistic, comprehensive, and applicable framework for the execution of human duties on earth.